2015
DOI: 10.3329/bjz.v41i2.23313
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyofauna of the river Halda, Chittagong, Bangladesh

Abstract: Eighty-three species of finfish belonging to 13 Orders, 35 Families, and 69 genera including three exotic species, and 10 species of shellfish (crustaceans) under one order, 3 families and 3 genera were identified from the River Halda during September 2004 to December 2011. Thus a total of 93 species of Ichthyofauna (finfish and shellfish) were recorded from this river during the seven years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) of investigation. Maximum number of finfish species were recorded under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…However, this problem is not rare in other part of Bangladesh and has been already reported by Galib et al (2013) and Mohsin et al (2013) who carried out researches on fish fauna in the Choto Jamuna River and the Padma River, respectively. The recorded fish species were lower than some other rivers of Bangladesh (Islam and Hossain, 1983;Hossain et al, 2007) but presence of similar number of fish species was also reported in the Halda River (Azadi and Alam, 2013). However, all the above mentioned researchers concluded with gradual loss of biodiversity in their considered rivers due to both natural and man-made causes.…”
Section: Fish Diversitymentioning
confidence: 66%
“…However, this problem is not rare in other part of Bangladesh and has been already reported by Galib et al (2013) and Mohsin et al (2013) who carried out researches on fish fauna in the Choto Jamuna River and the Padma River, respectively. The recorded fish species were lower than some other rivers of Bangladesh (Islam and Hossain, 1983;Hossain et al, 2007) but presence of similar number of fish species was also reported in the Halda River (Azadi and Alam, 2013). However, all the above mentioned researchers concluded with gradual loss of biodiversity in their considered rivers due to both natural and man-made causes.…”
Section: Fish Diversitymentioning
confidence: 66%
“…The river habitat is under extinction threat due to loop cutting in meanders, sand mining, blockage of flow by dams, sluice gates, embankments, pollution from paper mills, power plants, rubber dams over the river at upstream. Natural causes like siltation, erosion, climate change impacts are also influencing the changes in the river ecosystem [5]. Moreover, increased salinity in the Halda River has already posed a serious threat to city water supply over three dry seasons [6].…”
Section: Introductionmentioning
confidence: 99%
“…Halda River is one of the most important tributaries of the River Karnaphuli and is the only natural carp (Cyprinus carpio) breeding site of Bangladesh [1,2]. Carp fries collected from the river are the only natural breeding supplied to different divisions of Bangladesh for aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Dam constructions reduce water level at the downstream, which may negatively impact the ecological integrity of the river ecosystem by river sediment dynamics and morphology as well as water quality and habitat availability of aquatic [5,7]. The carp fish territory is under extinction risk because rubber dams, embankments, sluice gates, along with the loop cutting in meanders and waste discharge from paper and power plant industries at the river upstream are obstructing the minimum flow required for the carp habitats and spawning within the Halda River [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation